PENGARUH PENAMBAHAN TEPUNG BIJI DURIAN TERHADAP MIE BASAH BIJI DURIAN SEBAGAI MAKANAN JAJANAN ANAK SEKOLAH - Riris Oppusunggu (POLTEKKES KEMENKES MEDAN, 2021)
Elementary school children are one of the nutritionally vulnerable groups. This is because children are in a period of growth and development of bones, teeth, muscles and blood, so they need macronutrients such as energy, protein, fat and other nutrients. Noodles are a food that is very popular with the public, including toddlers and children. Its practical nature, relatively cheap price and easy way of serving it make this noodle product accessible to various levels of society. This study aims to determine the effect of adding durian seed flour to wet noodles as a snack for school children. This type of research is experimental, with a randomized experimental design used is a Completely Randomized Design (CRD) with 3 (three) treatments and 2 (two) repetitions. Data was collected by means of organoleptic tests, namely the color, texture, taste and aroma of durian seed wet noodles by 20 panelists. The results of the study were the color of wet noodles from durian seed flour was yellowish in color, chewy texture, taste was savory, aroma was fragrant. Overall, the wet noodles from durian seed flour that were most preferred by panelists were those who received treatment A with a ratio of wheat flour: seed flour. durian (90% : 10%). The conclusion is that the most preferred consumer acceptance of wet noodles is treatment A with 90% wheat flour and 10% durian seed flour.